(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
The aim of the following study is to investigate the relationship between foreign direct investment (FDI), high-tech exports and participation in innovation activities in Uzbekistan during 2008, 2024. We’ve constructed a synthetic IPI using macroeconomic indicators and firm-level data from the B-READY, and estimated traditional OLS as well as RandomForest and Extreme Gradient Boosting Classifier models to predict drivers of IPI. The evidence indicates that both inward FDI and growth of high-tech export are positively and significantly associated with innovation. The machine learning models expose non-linearities and confirm the dominance of FDI as a key driver.